PERANCANGAN LEARNING GAME INTERAKTIF MENGGUNAKAN METODE LINEAR SEQUENTIAL BERBASIS ANDROID - Dafid Kurniawan; Khairunnisa; Dharmawati (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2020)
The design of interactive games using the Android-based linear sequential method was aimed at students in grades 1 to 4 basic school. This game designing purposes to know various kinds of rare and unique animals that do not exist in their surroundings through quiz games, even in the garden, even the closest animal does not have a complete and unique animal. The designing of this interactive game is made by using 4 softwares, namely CorelDraw X4 software used to design gate, Adobe Photoshop to tidy up and change the .JPG format to .PNG, Construct 2 as the main software in design this game and the last one is Adobe PhoneGap Build which is a software online which functions to build files into .APK form so that this game can be played on android users. The process of design this game requires an idea and a sequence. The result of this game provide a new knowledge in order to add insight into various kinds of rare and unique animals that do not exist in the surrounding environment through a game where childern learn while playing.